عہد ِصحابہ کرام ؓ میں آداب اختلافات اور ان کا عملی اظہار -تحقیقی مطالعہ: "ETIQUETTES OF DISAGREEMENT AND THEIR PRACTICAL MANIFESTATION IN THE ERA OF THE COMPANIONS (RA) – AN ANALYTICAL STUDY" (Al-Aasar, 2025)
Disagreement is a natural phenomenon in any collective intellectual or social endeavor. In Islamic history, the Companions of the Prophet Muhammad (peace be upon him) represent a golden generation in which diversity of opinion was not only tolerated but respectfully managed within the framework of mutual reverence and adherence to Islamic principles. This paper explores the etiquettes of disagreement as practiced by the noble Companions (RA), highlighting key incidents, their reactions, and the moral and jurisprudential foundations of their approach. Through examining various scholarly and historical sources, the study aims to uncover how respectful dialogue, prioritization of unity, and avoidance of personal attacks were hallmarks of their disagreements. The findings of this research can offer valuable guidance in modern contexts of religious, social, and ideological differences..